Acute exposure to an electric field induces changes in human plasma lysophosphatidylcholine (lysoPC)-22:4 levels: Molecular insight into the docking of lysoPC-22:4 interaction with TRPV2. Issue 2 (2017) - Y, Nakagawa-Yagi; H, Hara; H, Nakanishi; T, Tasaka; A, Hara
No abstract available